Respon pertumbuhan dan hasil tanaman bawang merah (Allium ascalonicum) terhadap pemberian kompos limbah krisan - Retno Tri Purnamasari; Sulistyawati Sulistyawati; Fajar Hidayanto; Abdul Tholib (Fakultas Pertanian Universitas Majalengka, 2024)
Chrysanthemum waste compost fertilizer is an alternative to processing chrysanthemum waste, which has so far only been piled up on land and has yet to be processed into appropriate technology. The effectiveness of compost fertilizer was tested on shallots because this commodity is promising in every planting season. This study aims to determine the appropriate dose of chrysanthemum waste compost to produce optimum growth and yield of shallot plants. This research was conducted in Tidu Village, Pohjentrek District, Pasuruan Regency, at an altitude of ±12.5 masl from June to August 2022. The study used a randomized block design with 1 factor of four treatments and six replications. The treatment are P0 (without adding chrysanthemum waste compost as control), P1: (5ton ha-1 dose of chrysanthemum waste compost), P2 (10ton ha-1 chrysanthemum waste compost dose), and P3 (15ton ha-1 chrysanthemum waste compost dose). The results showed that applying 15 tons ha-1 of chrysanthemum waste compost gave the highest yield on tuber weight of 18.34 tons ha-1. It can be concluded that chrysanthemum waste compost influences the growth and yield of shallots. Applying chrysanthemum plant waste compost of 10 tons ha-1 showed optimal growth and yield of shallot plants. The dry weight of the resulting wind is 17.67 tons ha-1. This result exceeded the potential yield of the tubers of the varieties used, which ranged from 12-16 tons ha-1.